CORRUPTION DURING THE COVID-19 CRISIS RESPONSE IN UGANDA AND ITS IMPLICATIONS FOR THE RIGHT TO HEALTH - Mukiibi, Paul (Journal of Anti-Corruption Law, 2023)
Uganda’s Covid-19 crisis response involved the mobilisation of resources from the international community and the private sector. The Ugandan parliament also appropriated a supplementary budget towards the response. To expedite the procurement of essential goods and supplies by government agencies, some public procurement procedures were not followed. As a result, tender prices were rigged, and the quality of products supplied was compromised. Fake vaccines were also sold to unsuspecting recipients. This article contends that acts of corruption did not only compromise health outcomes but also denied potential beneficiaries the right to health. This was despite existing anti-corruption laws and legal institutions. Some corruption-related suspects were arrested and prosecuted.